Argentina, the expropriation of Repsol YPF, and the case for improved investment protection accords - Fredrik Erixon; Lisa Brandt (European Centre for International Political Economy (ECIPE), 2013)
Argentina's expropriation of Repsol's shares in the Argentinean energy company YPF sent chock waves through the international investment community. Even if the action by the government conformed to the standard of economic populism and nationalism that it is increasingly known for, the confiscatory nature of the expropriation was surprising. Subsequent actions by the government have also shown that it acted on ideological faith rather than taking a legitimate measure in the public interest. In contrast to the public case for the expropriation, the trade deficit in energy has continued to expand and the government has been forced to court international investors to team up with YPF to explore the rich shale reserves in Vaca Muerta. A second shock wave went through the international investment community when the government issued a decree to open up for international investments in the energy sector and allowed YPF to sign an agreement with Chevron to transfer some of the assets that are subject to the legal dispute between Repsol and Argentina. These actions change and reinforce the legal character of the expropriation - and it prompts governments to put more attention to improving the standards for international investment protection. The best approach now would be for the EU and the U.S. to negotiate a strong trade and investment accord that includes improved standards for investment protection. Other countries, especially those with a troubled record in investment disputes, may not be interested in revising their bilateral investment treaties with the EU and the U.S., but a transatlantic deal will change the politics of investment and incentivise other countries to agree to better standards.
Keywords: 330; Enteignung; Energiewirtschaft; Internationales Investitionsrecht; Argentinien